High Glucose Level Induces Cardiovascular Dysplasia During Early Embryo Development - Jin, Y.-m.; Zhao, S.-z.; Zhang, Z.-l.; Chen, Y.; Cheng, X.; Chuai, M.; Liu, G.-s.; Lee, K. K. H.; Yang, X. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The incidence of gestational diabetes mellitus (GDM) has increased dramatically amongst multiethnic population. However, how gestational diabetes mellitus damages the developing embryo is still unknown. In this study, we used yolk sac membrane (YSM) model to investigate angiogenesis in the developing chick embryo. We determined that in the presence of high glucose, it retarded the growth and extension of the embryonic vascular plexus and it also reduced the density of the vasculature in yolk sac membrane model. Using the same strategy, we used the chorioallantoic membrane (CAM) as a model to investigate the influence of high glucose on the vasculature. We established that high glucose inhibited development of the blood vessel plexus and the blood vessels formed had a narrower diameter than control vessels. Concurrent with the abnormal angiogenesis, we also examined how it impacted cardiogenesis. We determined the myocardium in the right ventricle and left atrium were significantly thicker than the control and also there was a reduction in glycogen content in cardiomyocytes. The high glucose also induced excess reactive oxygen species (ROS) production in the cardiomyocytes. We postulated that it was the excess reactive oxygen species that damaged the cardiomyocytes resulting in cardiac hyperplasia.
Keywords: gestational diabetes mellitus; cardiovascular system; ROS; YSM; CAM